Integration of non-SMAD and SMAD signaling in TGF-β1-induced plasminogen activator inhibitor type-1 gene expression in vascular smooth muscle cells - Samarakoon, Rohan; Higgins, Paul J. (Thrombosis and Haemostasis, 2008)
Overexpression of plasminogen activator inhibitor-1 (SER-PINE1, PAI-1), the major physiological inhibitor of pericellular plasmin generation, is a significant causative factor in the progression of vascular disorders (e.g. arteriosclerosis, thrombosis, perivascular fibrosis) as well as a biomarker and a predictor of cardiovascular-disease associated mortality. PAI-1 is a temporal/ spatial regulator of pericellular proteolysis and ECM accumulation impacting, thereby, vascular remodeling, smooth muscle cell migration, proliferation and apoptosis. Within the specific context of TGF-β1-initiated vascular fibrosis and neointima formation, PAI-1 is a member of the most prominently expressed subset of TGF-β1-induced transcripts. Recent findings implicate EGFR/pp60c-src→MEK/ERK1/2 and Rho/ROCK→SMAD2/3 signaling in TGF-β1-stimulated PAI-1 expression in vascular smooth muscle cells. The EGFR is a direct upstream regulator of MEK/ERK1/2 while Rho/ROCK modulate both the duration of SMAD2/3 phosphorylation and nuclear accumulation. E-box motifs (CACGTG) in the PE1/PE2 promoter regions of the human PAI-1 gene, moreover, are platforms for a MAP kinase-directed USF subtype switch (USF-1→USF-2) in response to growth factor addition suggesting that the EGFR→MEK/ERK axis impacts PAI-1 expression, at least partly, through USF-dependent transcriptional controls. This paper reviews recent data suggesting the essential cooperativity among the EGFR→MAP kinase cascade, the Rho/ROCK pathway and SMADs in TGF-β1-initiated PAI-1 expression. The continued clarification of mechanistic controls on PAI-1 transcription may lead to new targeted therapies and clinically-relevant options for the treatment of vascular diseases in which PAI-1 dysregulation is a major underlying pathogenic feature.
Keywords: SERPINE1; PAI-1; TGF-β1; epidermal growth factor receptor; EGFR; Rho kinase; SMADs; MAP kinases; transcription; pp60c-src; cardiovascular disease